Talking with your hands, listening with your eyes : a complete photographic guide to American Sign Language - Grayson, Gabriel (Garden City Park, NY : Square One Publishers, 2003)
Uses almost 1,400 photographs to present a comprehensive guide to the techniques, words, and phrases used in American Sign Language.
Includes index.
Keywords: American Sign Language; Deaf -- Means of communication -- United States; Deaf -- United States -- Social conditions